Long-acting muscarinic antagonists: a potential add-on therapy in the treatment of asthma? - William W. Busse; Ronald Dahl; Christine Jenkins; Alvaro A. Cruz (European Respiratory Review, 2016)
Asthma is a chronic inflammatory disorder of the airways that is a major global burden on both individuals and healthcare systems. Despite guideline-directed treatment, a significant proportion of patients with asthma do not achieve control. This review focuses on the potential use of long-acting anticholinergics as bronchodilators in the treatment of asthma, with results published from clinical trials of glycopyrrolate, umeclidinium and tiotropium. The tiotropium clinical trial programme is the most advanced, with data available from a number of phase II and III studies of tiotropium as an add-on to inhaled corticosteroid maintenance therapy, with or without a long-acting β2-agonist, in patients across asthma severities. Recent studies using the Respimat Soft Mist inhaler have identified 5 µg once daily as the preferred dosing regimen, which has shown promising results in adults, adolescents and children with asthma. Tiotropium Respimat has recently been incorporated into the Global Initiative for Asthma 2015 treatment strategy as a recommended alternative therapy at steps 4 and 5 in adult patients with a history of exacerbations. The increasing availability of evidence from ongoing and future clinical trials will be beneficial in determining where long-acting anticholinergic agents fit in future treatment guidelines across a variety of patient populations and disease severities.